Etika Pergaulan dalam Perspektif Al-Qur’an: Studi Analisis Surah Al-Hujurat Ayat 10-13 - Mawarni, Agus; Syawaluddin, Walid Huda; Nashiruddin, M.; Fachriansyah, Hafizh; Damanik, Agusman (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
In modern society, which is increasingly complex and interconnected, social ethics are crucial in forming harmonious relationships between individuals. In the Al-Qur’an, specifically in Surah Al-Hujurat verses 10-13, it presents teachings that urge Muslims to maintain social ethics with wisdom, fairness, and compassion. These verses provide guidance on the importance of mutual respect, peaceful conflict resolution, and refraining from mocking or ridiculing one another. The method used in this research is the method of Quranic exegesis or Historical Exegesis, which examines the historical context of the verses in Surah Al-Hujurat verses 10-13 (Mas'ud Maulana, Hidayatul Fikra, & Chodijah, 2022) to understand the conditions when these verses were revealed. This exegesis shows that these verses reinforce the values of social ethics, such as mutual respect, avoiding negative assumptions, and resolving conflicts with justice and peace. These verses provide concrete guidance for Muslims to interact with each other in their daily lives. In conclusion, Surah Al-Hujurat verse 10 emphasizes the importance of peaceful resolution in conflicts among fellow believers. Then, verse 11 emphasizes the prohibition of belittling others, teaches equality between men and women, and prohibits using derogatory names. Verse 12 also provides an example of safeguarding the honor of fellow Muslims. And in verse 13, it emphasizes awareness of piety as a determining factor of excellence in the sight of Allah.